2021
DOI: 10.1002/cbic.202100047
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Degradation of PARP14 Using a Heterobifunctional Small Molecule

Abstract: PARP14 is an interferon‐stimulated gene that is overexpressed in multiple tumor types, influencing pro‐tumor macrophage polarization as well as suppressing the antitumor inflammation response by modulating IFN‐γ and IL‐4 signaling. PARP14 is a 203 kDa protein that possesses a catalytic domain responsible for the transfer of mono‐ADP‐ribose to its substrates. PARP14 also contains three macrodomains and a WWE domain which are binding modules for mono‐ADP‐ribose and poly‐ADP‐ribose, respectively, in addition to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“… (Top) Compound 79 with its structure in complex with PARP14 (PDB ID 7L9Y ) and (bottom) its PROTAC derivative 78 ( 121 ) along with the IC 50 values against PARP14 and their selectivity profile. …”
Section: Alternative Strategies To Inhibit Mono-artsmentioning
confidence: 99%
See 1 more Smart Citation
“… (Top) Compound 79 with its structure in complex with PARP14 (PDB ID 7L9Y ) and (bottom) its PROTAC derivative 78 ( 121 ) along with the IC 50 values against PARP14 and their selectivity profile. …”
Section: Alternative Strategies To Inhibit Mono-artsmentioning
confidence: 99%
“…An alternative way to interfere with the enzyme would be through reducing the proteins levels with a PROTAC approach. Several PROTACs for poly-ARTs have been already reported as potent and efficacious to treat cancer, while only one degrader, has been developed for mono-ART PARP14 by Ribon Therapeutics, RBN12811 ( 78 ). The etherobifunctional degrader 78 (Figure ) was obtained by tethering the selective PARP14 inhibitor RBN12042 ( 79 ) to thalidomide through an appropriate linker.…”
Section: Alternative Strategies To Inhibit Mono-artsmentioning
confidence: 99%
“…While there is no inhibitor specific for a specific macrodomain, the compound GeA-69, interacting with ARTD8 macrodomain2, has been studied in lymphoma and myeloma, as well as for asthma treatment [121]. Ribon Therapeutics is studying the effects of their ARTD8 inhibitors: in vitro data showed that ARTD8 plays an immune-suppressive role in the tumor microenvironment, suggesting that ARTD8 targeting could generate an anti-cancer inflammatory response, similarly to results obtained by means of checkpoint inhibition [117][118][119][120][121][122][123]. A list of Macro-PARP inhibitors and application prospects to cancer treatment is presented in Table 3.…”
Section: Macro-parps: Artd7 Artd8 Artd9mentioning
confidence: 80%
“…In the beginning years, the developed inhibitors were designed targeting a group of ART enzymes; in recent years, novel compounds have been developed specific for a single ART enzyme, with effects at nanomolar concentration. For instance, there are new inhibitors targeting just ARTD10 [120,[127][128][129][130], ARTD11 [122,[131][132][133][134][135][136][137][138][139][140][141][142][143][144]. or ARTD14/PARP7 [142][143][144].…”
Section: Other Marylating Art Enzymes Linked To Cancer and Potential Enzyme Inhibitorsmentioning
confidence: 99%
“…62 ) based on a PARP14 inhibitor RBN012042. 398 The degrader 209 ( RBN012811 ) could selectively induce the degradation of endogenous PARP14 with DC 50 about 5 nM in KYSE-270 cells, and have no effect on the total protein levels of other PARP enzymes. It also could induce a dose-dependent reduction of IL-10 levels in primary human macrophages.…”
Section: Protacs Targeting Cancer-related Targetsmentioning
confidence: 99%